2018
DOI: 10.1016/j.neuroscience.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hit Compounds Identified from High-throughput Screening for their Effect on Blood–brain Barrier Integrity and Amyloid-β Clearance: In Vitro and In Vivo Studies

Abstract: In Alzheimer's disease (AD) the blood-brain barrier (BBB) is compromised, thus therapeutic targeting of the BBB to enhance its integrity and function could be a unique approach to treat, slow or hold the progression of AD. Recently, we have developed an in vitro high-throughput screening assay to screen for compounds that increase the integrity of a cell-based BBB model. Results from primary screen identified multiple hit compounds that enhanced the monolayer integrity. Herein, further characterization of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In addition, recent findings from our lab demonstrated etodolac to enhance the monolayer integrity in the absence and presence of Aβ oligomers (Qosa, Mohamed, Al Rihani et al, 2016); thus in this work, this experiment was performed in the absence of the stressor. Consistent with our previously published HTS studies (Qosa, Mohamed, Al Rihani et al, 2016;Elfakhri et al, 2018), etodolac and α-tocopherol each significantly enhanced tightness of the in vitro cell-based BBB model in a concentration dependent manner as demonstrated by reduction of the paracellular permeability marker 14 C-inulin across the bEnd3 monolayer when compared to the control (Fig. 1a).…”
Section: Improved Bbb Integrity Following Etodolac α-Tocopherol Andsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, recent findings from our lab demonstrated etodolac to enhance the monolayer integrity in the absence and presence of Aβ oligomers (Qosa, Mohamed, Al Rihani et al, 2016); thus in this work, this experiment was performed in the absence of the stressor. Consistent with our previously published HTS studies (Qosa, Mohamed, Al Rihani et al, 2016;Elfakhri et al, 2018), etodolac and α-tocopherol each significantly enhanced tightness of the in vitro cell-based BBB model in a concentration dependent manner as demonstrated by reduction of the paracellular permeability marker 14 C-inulin across the bEnd3 monolayer when compared to the control (Fig. 1a).…”
Section: Improved Bbb Integrity Following Etodolac α-Tocopherol Andsupporting
confidence: 91%
“…To determine the effect of etodolac, α-tocopherol, and combination on Aβ transport across the monolayer, transport study of 125 I-Aβ 40 (TQ B→A ) was performed as reported previously (Qosa, Abuasal et al 2014;Elfakhri et al, 2018). Each of the three treatments increased the transport of 125 I-Aβ 40 in a concentration-dependent manner (Fig.…”
Section: Increased Expression Of Major Aβ Transport Proteins and 125 mentioning
confidence: 83%
See 3 more Smart Citations